Digital tool as speech and language therapy for patients with post-stroke aphasia - Gerardo Ruiz Ares; Marta Martin Alonso; Ricardo Rigual; Carlos Hervás Testal; Gabriel Torres Iglesias; Laura Casado Fernandez; Elena de Celis Ruiz; Jorge Rodríguez Pardo; Jenny Carvajal Muñoz; Laura González Martín; María Alonso de Leciñana; Blanca Fuentes (Digital Health)
Introduction New technologies could play a role in post-stroke aphasia (PSA). Our aims were to develop a digital tool; to evaluate its acceptance and usability by patients and caregivers; and to demonstrate its effectiveness in improving language skills in patients with PSA, applying it from the acute phase. Methods The study consisted of two phases: development of a digital tool; and an interventional before-and-after study. During the first week of admission, the digital tool, VerbalizAPP ® , was installed for use with the help of family/caregivers. PSA was evaluated by a summarised version of the Boston Diagnostic Aphasia Examination (sBDAE) with 0–64 points. After 3 months of using VerbalizAPP ® , the sBDAE and scales to assess user satisfaction were applied. Results Forty patients (29 men, mean age 68.3 years) were included. Aphasia description: Broca's 12 (15.0%), Wernicke's 13 (32.5%), mixed/global 15 (37.5%) cases. Patients began using VerbalizAPP ® 4.8 days (range 2–7) after stroke onset. A significant improvement in sBDAE scores was found after 3 months of VerbalizAPP ® use: 35.1 (SD 17.6) versus 51.1 (SD 14.4) points; p  < .001. Academic level was the only baseline parameter related to outcomes. Comfort of use scored 8.8, and complexity 2.2 points. Expectations were exceeded in 61.1%, and impression of improvement in 83.3% of cases. No adverse effects were reported, and all participants would recommend VerbalizAPP ® to other patients. Conclusions Our results show the effectiveness of VerbalizAPP ® for the treatment of PSA. However, larger prospective validation studies should be conducted to recommend its widespread use.